A Green Pathway to Advanced Cobalt Oxide Materials: Dye Integration and Phytochemical Modification - Otah, Patricia Benedict; Nworie, Ikechukwu Christian; Echeweozo, Eugene; Ojebeagu, Augustine; Chikwendu, Augustine; Nwigwe, God`swill (International Journal of Applied Sciences and Smart Technologies, 2025)
This study investigated the impact of natural dyes derived from three plant sources (Eupatorium odoratum, Ageratum conyzoides, and Pueraria phaseoloides) on the bandgap energies of cobalt oxide (CoO) thin films thin films were synthesized using a chemical bath deposition technique at 80-85°C and subsequently annealed at 100°C, 150°C and 200°C. The incorporation of these natural dyes significantly influenced the bandgap energies of the CoO films, with values ranging from 3.80 eV to 4.12 eV depending on the dye and annealing temperature with the as-grown films exhibiting bandgap energies ranging from 3.80 eV to 4.00 eV. Moderate heat treatment typically increased the bandgap of the films, but at higher temperatures, the behavior became more complex, with some dyes demonstrating a substantial reduction in bandgap. These findings demonstrate the potential of utilizing natural dyes to effectively tailor the electronic structure of CoO, offering a sustainable and eco-friendly approach to materials modification.